2016
DOI: 10.1155/2016/8105163
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Class III Malocclusion in Growing Patients with Emphasis on Maxillary Protraction

Abstract: It is very difficult to diagnose and treat Class III malocclusion. This type of malocclusion involves a number of cranial base and maxillary and mandibular skeletal and dental compensation components. In Class III malocclusion originating from mandibular prognathism, orthodontic treatment in growing patients is not a good choice and in most cases orthognathic surgery is recommended after the end of growth. Approximately 30–40% of Class III patients exhibit some degree of maxillary deficiency; therefore, device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 84 publications
2
31
0
4
Order By: Relevance
“…Therefore, PFM treatment might contribute to the skeletal changes of TMJs. A three dimension assessment study showed that PFM lead to bone apposition at the anterior eminence of the TMJ and bone resorption at the posterior wall of the articular eminence, which correlated well with the posterior displacement of the condyle [ 29 , 30 ]. Meanwhile, continuous intermaxillary traction influenced the mandibular shape [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PFM treatment might contribute to the skeletal changes of TMJs. A three dimension assessment study showed that PFM lead to bone apposition at the anterior eminence of the TMJ and bone resorption at the posterior wall of the articular eminence, which correlated well with the posterior displacement of the condyle [ 29 , 30 ]. Meanwhile, continuous intermaxillary traction influenced the mandibular shape [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most systematic reviews and meta-analysis of PFM treatment mainly focused on its efficacy on Class III malocclusion, including the skeletal and dental changes [ 12 , 13 , 27 29 , 31 34 ]. Until now, no systematic review is available concerning the effect of PFM on TMJs, which has been a much debated issue among clinicians in the field of orthodontics.…”
Section: Introductionmentioning
confidence: 99%
“…What is the durability of the results achieved with this kind of therapy? The presented patient did not show the tendency for relapse for two years after the completion of the therapy, and the literature data point that relapse of class III primarily stems from mandibular growth, and not due to relapses in the maxilla [7].…”
Section: Discussionmentioning
confidence: 52%
“…In Asian population, majority of patients show deficit of the middle third of a face. According to literature, more than 60% of the cases of class III malocclusion occurred due to maxillary skeletal deficit [3,7,8].…”
Section: Introduction mentioning
confidence: 99%
“…For 3D position characteristics of an individual tooth within a denture, it is called micro level diagnostics, and relevant research results will improve the accuracy of the orthodontic treatment. In recent years, many authors have found that the bony cortex on the upper anterior labial side is thinner [ 1 , 7 ]; thus, during the adduction of the orthodontic treatment, if the thickness of the bony cortex is breached, there are frequent occurrences of bone fenestrations and dehiscence [ 8 ]. Therefore, a pre-alert has been raised due to the medical risks.…”
Section: Discussionmentioning
confidence: 99%